Prevention of sexual abuse in preschoolers - teacher’s knowledge and attitudes - Cascais, Mafalda (2020)
Introduction: Child sexual abuse (CSA) is a global public health problem across different culture and socioeconomic strata. Teachers have a privileged role in prevention programs and the approach is feasible and effective in preschoolers. The aim of this study was to characterize preschool teachers’ knowledge, attitudes, and training about CSA prevention. Methods: A non-experimental, exploratory, cross-sectional study was conducted in Leiria, Portugal, comprising 47 preschool teachers. Data was retrieved through a questionnaire developed by study authors. Results: Most preschool teachers had no CSA prevention training. About half of inquired teachers considered their knowledge about CSA prevention as reasonable. However, 12.8% classified it as poor, mainly teachers with less practice years (50% vs 69.6% of teachers with ≥30 practice years who classified their knowledge as reasonable, p=0.03). Most participants agreed that CSA prevention should be part of preschool curriculum, particularly older teachers (92% vs 77%, p=0.03). Most respondents considered adjusting these concepts to preschoolers challenging for implementation of prevention programs, 72.4% considered that some topics were not suitable for discussion with preschool children, and 82.9% considered that their approach was not well accepted by parents or caregivers. Discussion: Study results evidenced several difficulties and limited training of preschool teachers in CSA prevention. Encouragingly, most teachers showed a positive attitude towards participating in CSA training education and including this topic in preschool curriculum. This study emphasizes the importance of teachers’ education in this subject through implementation of training programs.